2012
DOI: 10.1111/j.1740-8709.2011.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary patterns, sedentary behaviour and overweight on the longitudinal development of childhood constipation: the Generation R study

Abstract: The influence of childhood nutrition on the development of constipation beyond the period of weaning and breastfeeding is relatively understudied. In addition, eating patterns in childhood can be highly correlated with overweight and sedentary behaviour, which may also have an influence on constipation. The aim of this study was to assess whether common dietary patterns, sedentary behaviour and childhood overweight are associated with constipation in childhood. The study was embedded in a population-based pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…32 Children were classified with functional constipation if they had experienced at least 1 of the following symptoms for at least 2 consecutive weeks: 2 or fewer bowel movements per week and predominantly hard/firm feces. 22 At age 6 years, children were classified with functional constipation if they met at least 2 of the following criteria for at least 2 consecutive weeks: 2 or fewer bowel movements per week, predominantly hard/firm feces, and fecal incontinence. 33 Analyses were adjusted for a number of sociodemographic (eg, sex, ethnic background, family income) and biobehavioral (eg, body mass index for age at the time of exposure, history of cow's milk allergy, maternal stress) factors (Table I), collected by postal questionnaires, from obstetric records, and during routine visits at the community well-baby clinics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Children were classified with functional constipation if they had experienced at least 1 of the following symptoms for at least 2 consecutive weeks: 2 or fewer bowel movements per week and predominantly hard/firm feces. 22 At age 6 years, children were classified with functional constipation if they met at least 2 of the following criteria for at least 2 consecutive weeks: 2 or fewer bowel movements per week, predominantly hard/firm feces, and fecal incontinence. 33 Analyses were adjusted for a number of sociodemographic (eg, sex, ethnic background, family income) and biobehavioral (eg, body mass index for age at the time of exposure, history of cow's milk allergy, maternal stress) factors (Table I), collected by postal questionnaires, from obstetric records, and during routine visits at the community well-baby clinics.…”
Section: Methodsmentioning
confidence: 99%
“…17 The etiology of functional constipation remains unclear but is likely multifactorial, involving genetic influences, behavioral factors such as physical activity, and dietary factors. [18][19][20][21][22] One of the most important dietary factors associated with constipation is low intake of dietary fiber. 23,24 A recent cross-sectional study reported a higher prevalence of "picky eating" among children with clinical constipation compared with healthy controls (27% vs 13%).…”
mentioning
confidence: 99%
“…The amount of DF which would be considered adequate for constipated children is unknown, but certainly it should not be lower than for healthy children (perhaps somewhat higher, instead), taking into account that most studies depicted a lower DF intake in constipated than in control children and, therefore, low DF intake is considered a risk factor for FC (4,23,42) . It was also shown that adherence to a 'Health Conscious' dietary pattern was associated with a lower prevalence of constipation at 24 months of age (43) , that there could be a bidirectional association between fussy eating and functional constipation in preschool children (44) and that picky eating was associated with a lower DF intake and hard stools (45) .…”
Section: Treatmentmentioning
confidence: 99%
“…Include prevention, starting at weaning (6,17,43) . Besides an adequate formula (whenever economically possible), complementary food containing DF according to Agostoni et al (41) should be recommended.…”
Section: Proposalsmentioning
confidence: 99%
“…40 Diets primarily comprising foods low in fiber, such as meat, bread, pasta, fried greasy foods, high sugar foods, and dairy products, may contribute to constipation. 4,46 The use of the terms such as 100% wheat, multigrain, stone-ground, cracked wheat, or bran does not mean that the product contains whole grain. 33 A patient friendly handout found in Figure 1 can help support the message of maintaining a healthy diet.…”
Section: Clinicalmentioning
confidence: 99%